Humoral factors in the formation of neuroosteoarthropathy in type 2 diabetes mellitus - M. M. Kalandiya; E. A. Kogan; L. V. Nikankina; A. Y. Tokmakova; E. L. Zaitseva; G. R. Galstyan (Сахарный диабет)
BACKGROUND: Diabetic neuroosteoarthropathy is a severe and insufficiently studied complication of diabetes mellitus, which is characterized by progressive destruction of bones and joints against the background of neuropathy and leads to the formation of foot deformities of varying severity. The search for predictors of this pathology is extremely relevant, because will optimize therapy and reduce the risk of limb amputation.AIM: To compare the levels of advanced glycation end products and their receptors in the blood and bone tissue in patients with type 2 diabetes mellitus and diabetic neuroosteoarthropathy and in individuals without this complication in order to determine the possibility of using these parameters as early predictors of severe foot deformities in this category of patients.MATERIALS AND METHODS: During hospitalization for planned surgical treatment, venous blood and bone tissue samples were taken from patients with chronic (inactive) stage of DNOAP and patients with neuropathic foot ulcers.RESULTS: The study included 88 patients with type 2 diabetes mellitus and neuropathic form of diabetic foot syndrome, who were divided into 2 groups. Group 1 consisted of patients with chronic diabetic neuroosteoarthropathy, group 2 — patients with severe diabetic neuropathy without osteoarticular disorders. The study did not show statistically significant differences in the level of AGE in the blood serum of patients with DNOAP and without this complication, however, a significant increase in AGE receptors (RAGE) in bone tissue was recorded in the group of patients with DNOAP compared with the control. Patients with increased RAGE expression in bone had higher blood levels of AGE compared to the group without this complication, but this difference was not significant.CONCLUSION: For the first time, a study of AGEs and receptors for them in the blood serum and bone tissue in individuals with DNOAP and without this complication was carried out. The obtained results suggest that the determining factor in the rate of formation and the likelihood of recurrence of DNOAP in type 2 diabetes mellitus is not the content of AGEs in the blood, but the expression of their receptors in bone tissue.